1993
DOI: 10.1017/s0021932000020691
|View full text |Cite
|
Sign up to set email alerts
|

Survival in the perinatal period: a prospective analysis

Abstract: A prospective study of 3080 Filipino mothers and non-twin births in 33 communities is used to study the determinants of mortality in week 1 postpartum. The results show significant nonlinear birth weight effects and the importance of environmental contamination, particularly for infants born by traditional methods at home, and several other intermediate and underlying determinants of perinatal mortality. The pathways through which important sociodemographic factors affect perinatal mortality are also presented. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Data from the Philippines have shown that birthweight is correlated both with survival during the neonatal period and with the risk of stunting in the first two years of life (Adair and Guilkey 1997; Popkin et al 1993). Birthweight is not only a marker of a successful pregnancy; it also affects the child's subsequent health.…”
Section: Midwives and Birthweightmentioning
confidence: 99%
“…Data from the Philippines have shown that birthweight is correlated both with survival during the neonatal period and with the risk of stunting in the first two years of life (Adair and Guilkey 1997; Popkin et al 1993). Birthweight is not only a marker of a successful pregnancy; it also affects the child's subsequent health.…”
Section: Midwives and Birthweightmentioning
confidence: 99%
“…This could partly be due to the fact that the most disadvantaged infants might have been lost from the sample due to early-life mortality and thus those who remained have only experienced relatively moderate adverse early exposures, thus reducing the explanatory power of predictors in the models. Previous research on this population, for example, has shown that infants with very low and high birthweight were more likely to die in the first week of life [91] so mortality-related attrition in this sample probably reduced the likelihood of finding significant relationships between early life conditions and adult immunophenotypes. The implications for morbidity, mortality, and other life history outcomes of the effects that we did identify in our analyses, however, are not clear.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the monthly mean precipitation is high in Hungary both in May and November [13]. In a prospective study of Filipino mothers, Popkin and colleagues found that seasonality was also a significant determinant of mortality during the first 7 days of life in the wet season [14]. Borchers and colleagues reported double peaks of respiratory syncytial virus (RSV) infection in spring and autumn in temperate regions [15].…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%